2014
DOI: 10.17645/si.v2i3.35
|View full text |Cite
|
Sign up to set email alerts
|

Policing Norwegian Welfare: Disciplining and Differentiating within the Bottom Rungs

Abstract: Policing is a disciplining means for using welfare services to govern welfare recipients towards a desired behaviour or goal. We apply Foucault's (1977) definition of institutional discipline as a means for exploring how the distinctions made by state and local welfare authorities in Norway when policing recipients may take shape according to normative perceptions of ethnicity and deservingness. More particularly, we explore the regulating understandings and activities linked to the inclusion and exclusion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Researchers have explored the configuration of crime control and migration control, conceptualised as 'crimmigration' (Barker, 2017), which is leading to the increasing criminalisation of migrants. Parallel to this, and to some extent embedded within one another, it is possible to clearly distinguish an increasing merge between social policy and labour policy, with higher demands towards racialised citizens participating in labour and language activities in order to obtain social assistance (Dahlstedt & Lalander, 2018;Gubrium & Fernandes, 2014). While it is the Swedish Public Employment Service that is responsible for implementing the government unemployment policies, the municipality is becoming a central actor within the unemployment area as municipalities are responsible for the unemployed that are dependent on social assistance (Vikman & Westerberg, 2017).…”
Section: Governing the Unemployed: Gendered And Racialised Discoursesmentioning
confidence: 99%
“…Researchers have explored the configuration of crime control and migration control, conceptualised as 'crimmigration' (Barker, 2017), which is leading to the increasing criminalisation of migrants. Parallel to this, and to some extent embedded within one another, it is possible to clearly distinguish an increasing merge between social policy and labour policy, with higher demands towards racialised citizens participating in labour and language activities in order to obtain social assistance (Dahlstedt & Lalander, 2018;Gubrium & Fernandes, 2014). While it is the Swedish Public Employment Service that is responsible for implementing the government unemployment policies, the municipality is becoming a central actor within the unemployment area as municipalities are responsible for the unemployed that are dependent on social assistance (Vikman & Westerberg, 2017).…”
Section: Governing the Unemployed: Gendered And Racialised Discoursesmentioning
confidence: 99%
“…Since 1964, Norwegian welfare has been directed towards work activation and reducing dependency on welfare state benefits (Gubrium and Fernandes 2014). When studies from the 1990s showed that large groups of immigrants were highly dependent on social welfare, debates emerged as to whether the benefits provided for this group supported their efforts to become self-sustained (Djuve 2011).…”
Section: Study Contextmentioning
confidence: 99%
“…In 2002, the Norwegian government passed the introduction law (Norwegian Government 2003), which included a mandatory introduction programme for groups of newly arrived immigrants to secure their participation in work and social life. Immigrants from Western countries were not included (Gubrium and Fernandes 2014). Participants in the programme are entitled to an individualized educational plan and each is assigned a programme advisor.…”
Section: Study Contextmentioning
confidence: 99%
See 1 more Smart Citation